Synthesis of Acrylonitrile Butadiene Styrene Membrane with Sulfonated Reduced Graphene Oxide and Cerium Filler - Siswantito, Firgi; Dampang, Sarah; Perdani, Meka Saima; Hakim, Muhammad Fahmi; Iskandar, Riska Listiarini (Universitas Islam Indonesia, 2025)
The study investigates the use of acrylonitrile butadiene styrene (ABS) polymer modified by sulfonated reduced graphene oxide (s-rGO) and cerium (Ce) as an alternative membrane to Nafion for Direct Methanol Fuel Cell (DMFC) applications. Pure ABS membranes and ABS membranes with s-rGO/Ce fillers were synthesized and characterized, with sulfonation at 60 °C using filler concentrations of 1%, 3%, and 5% v/v. The addition of fillers aimed to enhance ion exchange capacity (IEC), water absorption, and reduce methanol permeability. The membrane with 5% filler content showed optimal performance, with an IEC of 0.35 meq/g, a swelling degree of 1.5%, and controlled methanol permeability of 1.2670 × 10⁻⁷ cm²/s. FTIR analysis confirmed the presence of sulfonate groups (S=O) at 1054 cm⁻¹, indicating successful sulfonation. SEM analysis revealed that the filler was well-dispersed and formed more defined pores without compromising the structural integrity of the ABS matrix. This study demonstrates the potential of s-rGO/Ce-modified ABS membranes as a viable alternative to Nafion membranes in DMFC applications.